Dari Esoteris ke Literal: Penafsiran ar-Rāzī terhadap Huruf Muqatṭa'ah dalam al-Qur'an - Salsabila, Laily (Sunan Kalijaga Islamic State University, 2024)
Discussions about the muqatṭa'ah letters in the Qur’an frequently exhibit a historical bias, focusing predominantly on their linguistic attributes rather than their symbolic or contextual significance. Consequently, many pre-modern mufassirsoften neglect the functional role these letter combinations play, as well as the importance of historical and symbolic contexts in their interpretation. This research seeks to investigate how ar-Rāzī, a prominent pre-modern mufassir, employed context as a key element in interpreting the muqatṭa'ah letters. To achieve this, the study adopts Norman Fairclough's critical discourse analysis framework, which facilitates an examination of the complex discourse within Mafātiḥ al-Ghaib. The study's findings present two primary conclusions. Firstly, ar-Rāzī uses the association between the muqatṭa'ah letters and the subsequent words to establish five interpretative trends: as an indicator of the book, a symbol of the revelation process, a demonstrative word (ism isyārah), a pronoun (ism ḍāmir), and a symbol of the events represented in the text. This method reinforces the argument that the Qur'anic verses beginning with muqatṭa'ah letters underline the identity of the Qur'an as a revelation. Secondly, ar-Rāzī employs an intertextual approach, integrating his interpretations with the historical and cognitive discourse of his era, particularly through the lens of Asy'ariyah theology, which he embraced. By doing so, ar-Rāzī merges objective elements, such as grammatical functions, with subjective components, focusing on divine authority in understanding revelation. This dual approach allows ar-Rāzī to present an interpretation of the muqatṭa'ah letters that encompasses both esoteric and literal aspects, portraying the Qur'an as a text that is rich in both symbolic and historical meaning.